Change in Central corneal thickness after Phacoemulsification - Wali, Fariha Sher; Surhio, Sajjad Ali `; Talpur, Rafeen; Jawed, Muhammad; Shujaat, Shehnilla (Pakistan Journal of Ophthalmology, 2020)
Purpose: To determine changes in central corneal thickness after phacoemulsification at first post-operative day, one week and one month. Study Design: Descriptive Observational study. Place and Duration of Study: Sindh Institute of Ophthalmology and Visual Sciences, Hyderabad. From June 2018 to March 2019. Material and Methods: Ninety-two patients with ages between 35 and 72 years presenting with senile and pre-senile cataract were selected by non-probability convenience sampling. Patients with previous ocular surgery, ocular trauma, Glaucoma, Uveitis, Contact lens wear and long-term use of ocular medication were excluded. The patients were subdivided into three groups depending on variability in their corneal thickness. Patients with preoperative central corneal thickness (CCT) from 480 to 529µm were placed in group 1 (Thin), group 2 included patients with CCT ranging between 530 and 569µm (Moderate), patients with CCT from 570-640µm were placed in group 3 (Thick). Preoperative CCT was measured before extraction of cataract via phacoemulsification and then repeated on first post-operative day and then on one week and one month. Results: Preoperative mean central corneal thickness increased by 10.2% on first post-operative day. It reduced to 3.1% on seventh post-operative day. It further reduced to 0.7% on 30th post-operative day. Central corneal thickness reduced to mean value of 548.8µm on 30th post-operative day, which was statistically non-significant as compared with preoperative mean value (544.96µm). Conclusion: There was no statistically significant change in CCT one month after phacoemulsification when compared with the pre-operative CCT.